The Effect of Personality Traits And Congruity on Customer Satisfaction and Brand Loyalty on Janji Jiwa Coffee in Surabaya - Saifullah Saifullah; Dudi Anandya; Indarini Indarini (Program MM Universitas Surabaya, 2020)
The purpose of this research aims to prove the effect of personality traits and congruity to customer satisfaction and brand loyalty on Janji Jiwa in Surabaya. The type of research used is basic business research with causal objectives and quantitative research approaches. This research uses a purposive sampling approach with the sample is respondents aged 18 years and above and have consumed Samyang instant noodles. Respondents used in this study were 180 people. The analysis in this study is SEM (Structural Equation Modeling) and then processed using SPSS software version 20 for windows and also AMOS version 21.0 for windows used for testing the Measurement Model (Outer Model) and Structural Model (Inner Model). Keywords: personality traits, congruity, customer satisfaction, brand loyalty